Extruded Preparations with Sour Cherry Pomace Influence Quality and Increase the Level of Bioactive Components in Gluten-Free Breads - Dorota Gumul; Anna Korus; Rafał Ziobro (International Journal of Food Science)
Gluten-free bread (GFB) usually has a lower nutritional value than its traditional counterparts and is deficient in health-promoting substances. Therefore, GFB is often enriched in gluten-free components containing high levels of bioactive substances. In this work, an attempt has been made to enrich GFB with rice flour-based extruded preparations produced at 80 and 120°C with a share of 10 and 20% sour cherry pomace. The study material consisted of the abovementioned preparations together with breads produced with their 10% share. In order to prove that the extruded preparations could be the source of phenolic compounds, their level was determined. The influence of the applied additions was assessed taking into account nutritional composition (protein, fat, ash, and carbohydrates), level of the phenolic compounds (total phenolic content, flavonoids, anthocyanins, and phenolic acids), antioxidant potential, and physical properties of the breads (texture volume, color). It was shown that the extrudates with a share of fruit pomace cause an enrichment of gluten-free breads in bioactive compounds. The gluten-free breads enriched in extrudates with sour cherry pomace obtained at 120°C contained even 6 times more polyphenols than breads with extrudates obtained at 80°C. At the same time, these breads contained the highest levels of flavonoids and phenolic acids among all the analyzed samples. Bread with the addition of the extrudate produced with 20% fruit pomace at 120°C was the most favorable in terms of bioactive compounds (total phenolic content, flavonoids, anthocyanins, and phenolic acids) and antioxidative activity. The abovementioned bread showed the highest amount of total, soluble and insoluble fiber, and a significant amount of ash and sugars and revealed the lowest hardness during 3 days of storage, in comparison with the other samples.